Studies On The Biology And Activity Levels Of Carboxylesterase As An Indicator Of Insecticide Resistance In Populations Of Diamondback Moth, Plutella Xylostella (L.) (Lepidoptera: Plutellidae) On Cabbage in Ghana - Kaiwa, F.J. (University of Ghana, 2000)
Biology of Diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae) was studied in the laboratory under controlled conditions, i.e. 28 ±1 °C, 65-70 % r.h and a photoperiod of 12L: 12D hours. The results indicated that the developmental time of P. xylostella from egg to adult emergence took on the average 17.5 days. About 59 % of the eggs were laid on the first night of oviposition. Additionally females were generally larger (5.0mm) than males (4.5 mm). Effects of temperature, pH, and substrate concentration on the hydrolysis of a- naphthyl acetate by carboxylesterase from P. xylostella were evaluated. Optimum ranges of these parameters were, 40-45 °C for temperature, 6 9-7.3, for pH, and 35-40 mM for substrate concentration. Carboxylesterase analyses of P. xylostella populations collected around Accra indicated the probable incidence of insecticide resistance in the insect population. Carboxylesterase activity levels ranged from 2.06 to 28.29 nmol / 10min/μg protein. While the highest activity was recorded by populations from Kumoji Road and classified as moderately resistant, G.B.C (Ring Road) and Legon populations were classified as highly susceptible. The finding has enormous implications for the vegetable growers.